Svillen, Reinterpreting the Boathouse Clusters of Bohuslän - Landskap - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2024)
This thesis explores the potential of inserting contemporary architecture within the context of the Bohuslän archipelago. Through the design of a group of small buildings, based on in-depth studies of the architectural and typological features of local vernacular architecture, the thesis aims to revitalise the historical cluster typology through an architectural reinterpretation. More specifically the research focuses on ‘Sjöbodar ́ (fishermen’s boathouses). The research encompasses the sjöbod as an individual piece of traditional, vernacular architecture, including aspects of tectonics, as well as the proliferation of such buildings in larger groups or clusters. Within the cluster, a narrow, alley-like space is formed between the buildings, referred to as Svillen. Svillen is defined as the space closest to the boathouse, protected by an eave above. It was typically used as a place of practising labour, for storage, or drying nets, and was shared between the adjacent boathouses. Svillen has become of interest to the thesis as it raises questions concerning the role of the collective, i.e. the cluster, versus the role of the individual boathouse. Lastly, the thesis has explored the social culture in the clusters through the ‘Ljugarbänk’ (the liar’s bench) which is present in the stories about the fishing community. The design proposal consists of a cluster that is located in the Toftenäs nature reserve in southern Bohuslän. It houses common areas and accommodates temporary overnight stays for hikers and boaters, as it lies in a natural harbour. The design evokes the memory and identity of the fishing village through a reinterpretation of the traditional construction and building typology, and becomes a contemporary addition to the harsh coastal landscape. The proposal has explored design in 3 different scales; firstly, the detail in joinery and paraphrasing of Ljugarbänken, secondly, the Sjöbod as an individual piece of architecture, and lastly the cluster, including Svillen – the relationship between the buildings themselves and the sea.
Svillen, Reinterpreting the Boathouse Clusters of Bohuslän - Site
Keywords: Landskapsmodell; Sitemodel; Trä; Wood; 1:500; Svillen; CNC